Random Number and Combination Based Encryption and Decryption - Sneha K. Patel (International Journal of Mathematics And its Applications, 2017)
For secure communication, cryptography has been used for thousands of years. Encryption and decryption are the process of transforming plaintext into the ciphertext and vice versa. There are three types of encryption and decryption algorithms exist which are classified as symmetric key cryptography, asymmetric cryptography algorithm and hash function. This paper presents an algorithm for data encryption and decryption which is based on random number generation, combination and MOD operation. This algorithm uses random number and combinations, generate a key to encrypt or decrypt the data.